The research of gas tides intensification on the example of the sarmatian deposits in the northwestern part of Bilche–Volytska zone - Nesterenko, M. Yu; Balatskyi, R. S.; Zderka, T. V.; Piatkovska, I. O. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2015)
The article aims at the development and testing of the methods of gas flow intensification on the Sarmatian sediments samples of Bilche–Volytske zone. The existing standard methods for petrophysical study of reservoir rocks have served as the methodological basis for the implementation of research. Studies have been performed on three samples of reservoir rocks by modeling their contamination with drilling mud, resulting in the reduction of effective phase permeability of gas. The permeability of reservoir rocks has been restored with the help of modern foaming reagent, hydrochloric and acetic acid. Lithological and petrographic features of the samples have been considered to determine their role in the restoration of effective permeability of gas bearing Sarmatian sediments.